Effects of gestational diabetes mellitus with different birth weight on genetic metabolism of newborns. A retrospective cohort study - Dandan Xia; Huiyan Wang; Yuqi Yang; Wenli Wang (Ginekologia Polska)
OBJECTIVES: To investigate the effects of gestational diabetes mellitus (GDM) with different birth weights on neonatal genetic metabolism. MATERIAL AND METHODS: 1252 patients with GDM diagnosed at Changzhou Maternal and Child Health Care Hospital from 2017 to 2021 were categorized into three groups: fetal growth restriction (G1), normal birth weight (G2), and macrosomia (G3). The levels of amino acids, free carnitine (CO) and acylcarnitine in neonates were detected using tandem mass spectrometry. RESULTS: There were no differences in age, height, predelivery weight or gravida across groups. G3 had the highest parity and fasting blood glucose levels (p < 0.0001). G1 exhibited the highest rates of cesarean section, neonatal asphyxia, and insulin utilization (p < 0.0001). Neonatal genetic metabolism analysis revealed that in G1 citrulline levels were the highest, with significantly elevated levels of leucineornithine and valine (p < 0.001). CO was also the highest (p < 0.001). The levels of isovalerylcarnitine, octanoylcarnitine and 18-carbodienoylcarnitine increased, while malonylcarnitine/3-hydroxy-butyrylcarnitine, hexadecanoylcarnitine, hexadecenoylcarnitine, 3-hydroxy-hexadecenoylcarnitine and 3-hydroxy-hexadecanoylcarnitine decreased (p < 0.05). In G2, methionine levels decreased (p < 0.001), whereas decenoylcarnitine, dodecanoylcarnitine, dodecenoylcarnitine and myristoylcarnitine levels increased (p < 0.001). In G3, proline decreased significantly (p < 0.001), and CO was the lowest (p < 0.001). Propionylcarnitine and octenoylcarnitine levels increased, whereas butyrylcarnitine decreased (p < 0.05). CONCLUSIONS: Gestational diabetes mellitus with different birth weights influences neonatal genetic metabolism in distinct ways. Therefore, neonatal screening for inherited metabolic disorders provides insights into the metabolic levels of offspring of patients with GDM in early life.